Using Facebook as a Communication Tool in Agricultural-Related Social Movements - Mica Graybill-Leonard; Courtney Meyers; David Doerfert; Erica Irlbeck (Journal of Applied Communications, 2011)
A social movement is a personal obligation taken on by an individual, due to either a personal experience or responsibility, to pursue action to implement a change in a community or society. Facebook is a social networking device in which users interact through conversations, and build relationships by networking with other users. Facebook groups are created as part of a smaller community within the social networking site and focus on particular interests or beliefs about certain issues. The purpose of this study was to determine why individuals use social media, specifically Facebook, to communicate information in social movements related to agricultural issues. Eight semi-structured interviews were conducted with Facebook group administrators who actively contribute to the promotion of an agricultural-related social movement. Results indicated that Facebook was a beneficial communication tool to help the social movements reach more individuals. The Facebook group administrators were motivated to become involved with the social movement due to personal experiences. Although Facebook is the primary method used to reach target audience members, the participants said they use a variety of other communication channels. Additional research should explore other social movements to determine the impact social media has on communication efforts.
Keywords: social movement; social media; Facebook; interviews; online communication